the best way to solve this is using a system. let's pretend the two numbers we have are notated using the variables x and y.
our first equation is this:
x + y = -46. the sum of the two numbers x and y is -46.
our first equation is this:
x + 13 = y. here, the variable doesn't really matter. so, what this says is that y is 13 greater than x.
now, you know how to represent y in terms of x. plug the second equation into the first and you get this:
x + ( x + 13) = -46.
solve this:
2x + 13 = -46
2x = -59
x = -29.5
now, we know what x equals. using the second equation we created,
x + 13 = y, we can figure out what y equals. so, let's plug x in.
-29.5 + 13 = y
y = -16.5
you've got x and y now! i hope i helped you.
xoxo